Changes in substance use and engagement in gaming/gambling in persons with severe mental illness during the COVID-19 pandemic and earthquakes: a community study in two points - Medved, Sara; Palavra, Irena Rojnić; Gerlach, Josefina; Levaj, Sarah; Shields-Zeeman, Laura; Bolinski, Felix; Bradaš, Zoran; Madžarac, Zoran; Filipčić, Igor; Rojnić Kuzman, Martina (Frontiers in Psychiatry, 2023)
External stressors, such as COVID-19 pandemic and earthquake, can cause an increase in substance use and addictive behaviour in persons with severe mental illnesses (SMI). We analyzed the changes and predictors of substance use and addictive behaviour in SMI during these double disasters in Croatia. Questionnaires exploring the presence of substance or behaviour addiction disorder, mental ill-health (Depression Anxiety Stress Scales-21 (DASS-21), Insomnia Severity Index (ISI), Perceived Stress Scale (PSS), Obsessive-Compulsive Inventory-Revised), coping mechanisms, and perceived social support (Multidimensional Scale of Perceived Social Support, MSPSS) were administered among 90 participants with SMI included in the RECOVER-E study in May/June 2020 (first COVID-19 wave, Zagreb earthquake) and in December 2020/January 2021 (second COVID-19 wave, Petrinja earthquake). In both time points, a major increase was observed in tobacco smoking (25.0%; 28.6%, respectively) predicted by discontinuation of antidepressants and higher DASS-21 score. Increased sedative use was observed (24.4%; 23.8%, respectively) predicted by higher PSS and ISI scores, lower MSPSS scores, antipsychotic discontinuation and not receiving community mental health team (CMHT) service. In persons with SMI during a double disaster special attention needs to be given to reducing mental-ill health and stress, providing social support and continuity of psychiatric care, through medications and CMHTs.